Solve the factored quadratic equation (x−5)(x+3)=0

.(1 point)

1 answer

To solve the factored quadratic equation \((x - 5)(x + 3) = 0\), you can use the zero product property, which states that if the product of two factors is zero, then at least one of the factors must be zero.

Set each factor equal to zero:

  1. \(x - 5 = 0\)
  2. \(x + 3 = 0\)

Now, solve each equation:

  1. For \(x - 5 = 0\): \[ x = 5 \]

  2. For \(x + 3 = 0\): \[ x = -3 \]

The solutions to the equation \((x - 5)(x + 3) = 0\) are \(x = 5\) and \(x = -3\).

Similar Questions
  1. 1)What method(s) would you choose to solve the equation:x2 + 2x - 6 = 0 A. Square roots; there is no x-term. B. Quadratic
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. 4. Solve the factored quadratic equation (19x−3)(9+x)=0. Enter the lesser number first.(2 points) The solution set is { , }
    1. answers icon 1 answer
more similar questions